Diagnosis of the digitalization of intraparty democracy in Southern European political parties - Sánchez Medero, Gema (Frontiers in Political Science, 2025)
The purpose of this study is to diagnose levels of intraparty digital democracy on Southern European political parties’ official websites and digital platforms. To this end, an intraparty digital democracy index has been developed to measure intraparty digital democracy beyond the scope of candidate selection and general participation, using the variables established by the Varieties of Democracy index as a reference. In this way, it is possible to determine whether the digitalization of parties is truly altering parties’ behaviors towards, and interactions with, members, based on the premise that democratization involves different costs, trade-offs, and challenges. This has led us to ask which dimensions are undergoing the most digitalization, why this is and, whether the origin of the parties becomes a determining factor for greater democratization of these.